Three-Port Full-Bridge Converters with Varied Voltage Input for Solar Power Systems (International Journal of Engineering and Computer Science, 2014)
A systematic method for deriving three-port converters (TPCs) from the full-bridge converter (FBC) is proposed in this paper. The proposed technique splits the two switching legs of the FBC into two switching cells with different sources and allows a dc bias current in the transformer. By using this systematic technique, a novel full-bridge TPC (FB-FBC) is developed for renewable power system applications which feature simple topologies and control, a reduced no. of devices, and single-stage power conversion between any two of the three ports. The proposed FB-TPC contains of two bidirectional ports and an isolated output port. The main circuit of the converter functions as a buck-boost converter and provides a power ﬂow path between the ports on the primary side. The FB-TPC can adapt to a varied source voltage range, and tight controller over two of the three ports can be achieved while the third port provides the power balance in the system. Also, the energy stored in the leakage inductance of the transformer is utilized to achieve zero-voltage switching for all the primary-side switches. The FB-TPC is analyzed in detail with working principles, design considerations, and a pulse-width modulation scheme (PWM), which aims to decrease the dc bias of the transformer.